DEBT MANAGEMENT: STRATEGIES TO MINIMISE FINANCIAL RISK - Abdul Rosid (Adisam Publisher, 2025)
Debt management: Strategies to minimize financial risk are a set of practices and strategies implemented by an individual or company to effectively manage debt. The goal is to meet payment obligations on time, reduce liquidity and credit risks, and stabilize debt costs by diversifying financing sources and using hedging instruments. The research methodology was conducted using a literature review approach. The results of this study indicate that good cash flow management is a key factor in minimizing liquidity risk, including measures such as aligning debt repayment plans with income sources and maintaining adequate cash reserves. Diversified funding sources have also been shown to be effective in reducing concentration risk and reliance on a single loan type or creditor, while hedging instruments such as interest rate swaps and foreign exchange forwards help stabilize borrowing costs. In addition, the results show that consistent and structured credit assessments can strengthen credit risk control and reduce default risk. Companies that actively assess their own credit and use detailed credit reports are better able to handle credit issues. The use of scenario analysis and stress models in risk profile management also provides important insights to support better decision-making.